Improving the Quality of Life for Autistic Children through Mobile-Based Learning and Developmental Monitoring - Hidayat, Luqman; Hasanah, Laeli Nur; ., Rianto (Journal of Cultural Analysis and Social Change, 2025)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder with increasing prevalence worldwide. This disorder significantly impacts not only children diagnosed with ASD but also their families, posing challenges in daily life, education, and social integration. Digital support technology, especially mobile applications, has emerged as a valuable tool for providing comprehensive support to children with autism and their families, ultimately enhancing the quality of life for children with autism. This study aims to develop and evaluate the effectiveness of mobile applications in enhancing the development of children with autism, particularly in gross motor skills, fine motor skills, communication skills, problem-solving abilities, and social skills. This research adopted the ADDIE model framework, comprising Analysis (A), Design (D), Development (D), Implementation (I), and Evaluation (E). An interactive mobile application was developed to address the specific educational and developmental needs of children with autism. The effectiveness of the application was evaluated using Welch's test. The study resulted in the development of the AutiParent mobile application, which integrates various features, including health services, educational modules, social support, child profiles, health screening and monitoring, social skills training, educational games, communication tools, structured schedule recording, and community interaction support. The application’s effectiveness was tested over five months, revealing a statistically significant improvement in children's developmental skills across all tested areas. Statistical analysis using Welch's t-test demonstrated a p-value <0.05 for all indicators, confirming a significant difference between the first and fifth months. The consistently higher average scores in the fifth month indicate significant improvements in all assessed developmental aspects. This study provides empirical evidence supporting the use of digital interventions to enhance the developmental skills and quality of life of children with ASD and their families. The findings highlight the potential of mobile applications as accessible, cost-effective, and personalized tools for structured learning and developmental monitoring.